2020
DOI: 10.1007/s40820-020-00465-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft Mesoporous Organosilica Nanoplatforms Improve Blood Circulation, Tumor Accumulation/Penetration, and Photodynamic Efficacy

Abstract: To date, the ability of nanoplatforms to achieve excellent therapeutic responses is hindered by short blood circulation and limited tumor accumulation/penetration. Herein, a soft mesoporous organosilica nanoplatform modified with hyaluronic acid and cyanine 5.5 are prepared, denoted SMONs-HA-Cy5.5, and comparative studies between SMONs-HA-Cy5.5 (24.2 MPa) and stiff counterparts (79.2 MPa) are conducted. Results indicate that, apart from exhibiting a twofold increase in tumor cellular uptake, the soft nanoplatf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The high-efficiency transportation to LNs is supported by our previous finding that SMON nanoplatforms have remarkable tissue penetration. [39] Based on these results, SMONV promotes antigen delivery into draining LNs, which maximizes antigen exposure in the lymphatic system and enhances DC-mediated T-cell immune responses.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The high-efficiency transportation to LNs is supported by our previous finding that SMON nanoplatforms have remarkable tissue penetration. [39] Based on these results, SMONV promotes antigen delivery into draining LNs, which maximizes antigen exposure in the lymphatic system and enhances DC-mediated T-cell immune responses.…”
Section: Resultsmentioning
confidence: 96%
“…The mechanism of SMON obtained by preferential etching of MON has been reported in our previous work. [38,39] Briefly, MON, which is synthesized using a CTABdirected sol-gel process, has a more stable outer layer because the Si-OH group on its surface is highly cross-linked by ammonia catalysis. When MON is dispersed in a NaOH solution, the less condensed cores and the inorganic silica species in the shell are preferentially etched by OH − , leading to a significant increase in the proportion of flexible Si-R-Si chains and noncross-linked free Si-OX groups in the overall framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…fabricated hollow soft shell MONs by selectively etching a portion of the silica from the thioether hybridized framework. [ 124 ] The obtained soft MONs with hyaluronic acid as surface ligands had a hollowed structure and wrinkled morphology, featuring a much lower Young's modulus (24.2 MPa) than their rigid counterparts (79.2 MPa). The in vitro results indicated that the soft MONs had increased cellular uptake and deeper tumor penetration depth in 3D tumor spheroids of MCF‐7 cancer cells.…”
Section: Tuning Siliceous Framework By Incorporation Of Organic Speciesmentioning
confidence: 99%